Critical success factors of women entrepreneurship practice for women entrepreneurs in Malaysia - Ong, Sharon Yong Yee; Habidin, Nurul Fadly; Salleh, Mad Ithnin; Mohd Fuzi, Nursyazwani (Inderscience Publishers, 2021)
The purpose of present study is to analyses the critical success factors of WEP implementation in Malaysia. The study indicates six critical success factor of WEP (entrepreneurial traits, entrepreneurial experience, management skill, customer relation, training and education and environment). A total of 38 responses from women entrepreneurs in Malaysia were collected through email and on-line questionnaires. The result shows the mean values are 5.811 to 5.461, consider good at WEP implementation. The dimension TE (5.811) and EE (5.758) have the highest mean value and shown to be the most important dimensions of WEP implementation for women entrepreneur in Malaysia SMEs. The implications present study is anticipated to help better understand women entrepreneurs' condition, needs and provide new insights for the critical success factors of a more gender-specific practice for women entrepreneurs in Malaysia. This study also provides important guidelines to implement WEP. In future research, the relationship between WEP and business performance of women entrepreneur in Malaysia will be analyses and then compare the results to other countries.